2019
DOI: 10.1097/cm9.0000000000000489
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with progression to intestinal complications of Crohn disease

Abstract: Background:Crohn disease is a chronic bowel disease that causes serious complications. Prevalence of Crohn disease is increasing. Studies have shown that the behavior of the disease is not stable and severe complications secondary to behavior change over time have been shown. In this study, we aimed to evaluate the prognostic risk factors associated with phenotypic change in Crohn disease in a Turkish patient cohort.Methods:Patients followed up from March 1986 to August 2011 were evaluated for demographic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Besides, we found that smoking status was not related to the disease behaviour of Crohn’s disease after the first surgery, which was consistent with a previous report [34]. Several studies have demonstrated that perianal disease is a predictor of likelihood and time to progression of Crohn’s disease behaviour [24,35]. The Crohn’s disease patients with perianal disease had a higher risk of changing to ileocolonic disease, which may be due to the presence of perianal lesions, which aggravated the disease that expanded the intestinal involvement.…”
Section: Discussionsupporting
confidence: 91%
“…Besides, we found that smoking status was not related to the disease behaviour of Crohn’s disease after the first surgery, which was consistent with a previous report [34]. Several studies have demonstrated that perianal disease is a predictor of likelihood and time to progression of Crohn’s disease behaviour [24,35]. The Crohn’s disease patients with perianal disease had a higher risk of changing to ileocolonic disease, which may be due to the presence of perianal lesions, which aggravated the disease that expanded the intestinal involvement.…”
Section: Discussionsupporting
confidence: 91%
“…Our study included nearly 6000 patients; a sample size substantially larger than most studies in CD to date and in a dataset not described previously, namely, Spanish patients [ 48 , 49 ]. Notably, the clinical characteristics of patients with CD reported here were in line with results using traditional methods [ 48 , 49 ], validating the use of our technology. Here, disease behavior (phenotype) was defined mostly as an inflammatory disease (i.e., nonstricturing and nonpenetrating disease) [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…9-11 The increase in ECM production in SCD is compounded by the reduced expression of enzymes that degrade collagen (matrix metalloproteinases (MMPs) and increased expression of tissue inhibitors of MMPs (TIMPs). 1 The molecular mechanisms underlying SCD are complex, incompletely described and influenced by environmental triggers and genetic susceptibility 12-14…”
Section: Introductionmentioning
confidence: 99%